Healthcare and Disease Burden in Africa The Impact of Socioeconomic Factors on Public Health - Niohuru, Ilha.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open access book evaluates African healthcare systems from multiple perspectives. By examining empirical data from various African countries, it analyzes the effects of socioeconomic factors such as urbanization, population growth, and education on various health indicators, including the situation of health professionals, patients's decision making, health resource distribution, mortality rates, and the burden of disease. Furthermore, topics such as the use of social media in healthcare and insurance policy in Africa are addressed. This book appeals to scholars and professionals interested in healthcare in Africa.
Chapter 1. Introduction -- Chapter 2. Country Demographics -- Chapter 3. Disease Burden and Mortality -- Chapter 4. Health Resource -- Chapter 5 Healthcare Affordability -- Chapter 6. Social Media and Technology Use -- Chapter 7. Conclusion.
Keywords: Medical economics; Public health; Medicine, Preventive; Health promotion; Health services administration; Public health administration; Health Economics; Public Health; Health Promotion and Disease Prevention; Health Care Management; Health Administration